A simple technique can reduce cardiopulmonary bypass use during lung transplantation - Samano, Marcos N. (2016)
Cardiopulmonary bypass causes an inflammatory response and consumption of coagulation factors, increasing the risk of bleeding and neurological and renal complications. Its use during lung transplantation may be due to pulmonary hypertension or associated cardiac defects or just for better exposure of the pulmonary hilum. We describe a simple technique, or open pericardium retraction, to improve hilar exposure by lifting the heart by upward retraction of the pericardial sac. This technique permits lung transplantation without cardiopulmonary bypass when bypass use is recommended only for better exposure.